Fish Community in Different Mangrove Habitat in Banyuurip Ujung Pangkah – Gresik Regency - Rohmawati, Vivi Dwi; Latuconsina, Husain; Zayadi, Hasan (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
The research was conducted at Banyuurip Mangrove Center, Ujung Pangkah District, Gresik Regency, East Java, during July-August 2020. Determination of purposive sampling locations based on physical differences in mangrove habitats. Systematic sampling method was used to estimate the number of mangrove species using belt transects. Fish sample collection uses basic gill nets that are placed at high tide in each mangrove habitat. The results showed that the total number of individual mangrove vegetation was 505 from 12 species, the number of species and individual mangrove vegetation differed between habitats, and the highest was found in coastal mangrove habitats. The number of fish was found as many as 181 individuals from 11 species, 10 families and 5 orders. The number and composition of species, families and fish orders differ between mangrove habitats, with the highest number in coastal mangrove habitats.